Closure of a persistant oroantral fistula with nasoseptal cartilage as a complication of lateral sinus lifting: A case report - Gürler, Gökhan; Dilaver, Emrah; Soylu, Erkan; Develi, Tuba; Delilbaşı Barış Çağrı (My University, 2017)
Oroantral fistula may develop due to tooth extraction, infection or surgical interventions in the posterior maxilla. Several surgical techniques have been described for oroantral fistula closure. All these techniques have different advantages and disadvantages. This report presents an oroantral fistula case, which occurred, following lateral sinus lifting procedure. Traditional surgical techniques (buccal advancement flap, palatal flap, and Bichat's buccal fat pad) were performed to close the oroantral fistula, but could not to be managed. Finally, closure was succeeded with septal cartilage graft placed over the bony defect.

Oroantral fistül, posterior maksillada diş çekimi, enfeksiyon veya cerrahi işlemlere bağlı olarak gelişebilir. Oroantral fistülün kapatılmasına yönelik pek çok cerrahi teknik tanımlanmıştır. Bütün bu tekniklerin kendine özgü avantaj ve dezavantajları vardır. Bu olguda raporunda lateral sinüs yükseltme işlemine bağlı gelişen oroantral fistül sunulmuştur. Geleneksel cerrahi yöntemlerle (bukkal ilerletme flebi, palatal flep, Bichat bukkal yağ dokusu) kapatılamayan defekt, son olarak otojen septal kıkırdak grefti uygulanarak başarıyla kapatılabilmiştir.
Lateral sinus yükseltme komplikasyonu olarak oluşan inatçı oroantral fistülün nazoseptal kıkırdak ile kapatılması: Bir olgu sunumu
Keywords: Oroantral Fistula; Sinus Lifting; Septal Cartilage; Complication; Oroantral Fistül; Sinus Yükseltme; Septal Kıkırdak; Komplikasyon